2022
DOI: 10.1139/cjpp-2021-0330
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of rupatadine against l-arginine-induced acute pancreatitis in rats: role of inflammation

Abstract: Acute pancreatitis (AP) is an abrupt inflammatory disorder causing high morbidity and mortality. As AP is an insidious medical emergency, a curative modality is required instead of a preventive measure. Thus, we investigated the possible curative effect of rupatadine on a rat model of AP. Rupatadine is a potent histamine receptor 1 (H1R) and platelet-activating factor (PAF) blocker. We used four groups of six Wistar rats as follows: the control group received vehicle; the rupatadine control group received rupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…RUP previously alleviated ROS-induced hepatocyte and intestinal apoptosis (Mohamed and Mohammed 2021). Besides, the anti-oxidant activity of RUP was demonstrated in rats with acute pancreatitis and diabetic nephropathy as well as in allergic rhinitis in patients (Hafez et al 2020;Kahveci et al 2021;Mohamed et al 2022). Based on these findings, the anti-oxidant activity of RUP could be postulated to prevent ROS-induced fibrosis.…”
Section: Discussionmentioning
confidence: 89%
“…RUP previously alleviated ROS-induced hepatocyte and intestinal apoptosis (Mohamed and Mohammed 2021). Besides, the anti-oxidant activity of RUP was demonstrated in rats with acute pancreatitis and diabetic nephropathy as well as in allergic rhinitis in patients (Hafez et al 2020;Kahveci et al 2021;Mohamed et al 2022). Based on these findings, the anti-oxidant activity of RUP could be postulated to prevent ROS-induced fibrosis.…”
Section: Discussionmentioning
confidence: 89%
“…Although the results of the RP-treated cells were not further examined in this study, a recent in vivo study has demonstrated that RP exhibits important anti-inflammatory and anti-apoptotic effects against l -arginine-induced acute pancreatitis by reducing the expression of nuclear factor kappa-B (NF-κB) and caspase 3, with the latter playing a crucial role in the apoptosis cascade that is anticipated upon p53 activation. 62 , 63 A confluence of the anti-apoptotic effects due to caspase 3 downregulation and the pro-apoptotic effects due to MDM2 inhibition could contribute to the near-basal/down-regulated levels of BAX , CDKN1A , and DDB2 expression in the RP-treated U87 cell lines. Despite the relatively low IC 50 dose, the same mechanism might not be as effective in the SH-SY5Y cell lines, hence the increased BAX and DDB2 expression but the decreased level of CDKN1A expression.…”
Section: Discussionmentioning
confidence: 99%
“…4). Although the results of RP-treated cells were not further examined in this study, a recent in vivo study has demonstrated that RP exhibits important anti-in ammatory and anti-apoptotic effects against l-arginine-induced acute pancreatitis by reducing the expression of nuclear factor kappa-B (NF-κB) and caspase 3, the latter playing a crucial role in the apoptosis cascade which is anticipated upon p53 activation [58,59]. A con uence of anti-apoptotic effects due to caspase 3 downregulation and pro-apoptotic effects due to MDM2 inhibition could contribute to the near-basal/down-regulated levels of BAX, CDKN1A, and DDB2 expression in RP-treated U87 cell lines.…”
Section: Discussionmentioning
confidence: 99%